Analisis Perspektif Komparatif Regulasi Hukum Dagang Nasional dengan Standar Internasional - Pesman Laia; Hudi Yusuf (CV. ITTC INDONESIA, 2024)
In the context of an increasingly interconnected global economy, international trade plays a crucial role as one of the cornerstones of a nation's economic growth. However, there often exists a disparity between national trade law regulations and international standards, posing challenges in regulating cross-border trade. This study aims to explore the differences, compatibility, and challenges arising from the implementation of national trade law regulations in light of international standards. Employing a method of document comparison analysis, relevant documents from specific countries and related international organizations have been collected and thoroughly analyzed. The findings of this analysis are expected to provide a deeper understanding of the extent to which national regulations support or contradict international standards, while also offering recommendations to enhance the alignment between national trade law regulations and international standards. Thus, it is anticipated that the outcomes of this research will significantly contribute to enriching the understanding of the relationship between national trade law regulations and international standards in the context of international trade.